2013
DOI: 10.1002/pssb.201349154
|View full text |Cite
|
Sign up to set email alerts
|

Atomic H interaction with the γ‐U (100) surface

Abstract: Theoretical analysis of the adsorption of a H atom on the (100) surface of bcc γ‐U represented by a 5 layer slab indicates an exothermic reaction with the bridge site as the preferred site with a chemisorption energy of 3.80 eV at the relativistic level of theory with spin–orbit coupling (SOC) included. The ground state magnetic configuration of the UH system is found to be nonmagnetic, in agreement with experimental results for UH3. The change in work function of the slab with the addition of the H atom is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Similar results have been seen with materials containing lower-Z metals, where inclusion of GGA + U had a minimal effect on surface energy ordering . In addition, uranium phases are known to exhibit magnetic moments at their surface, which can affect surface adsorption energies. In order to assess these effects on α-U surface properties and hydrogen adsorption, we have chosen to perform a bounding study using PBE on the faceted (012) and (102) surfaces, which are the two highest energy/most reactive surfaces studied in our work (see Section for further discussion).…”
Section: Resultssupporting
confidence: 71%
“…Similar results have been seen with materials containing lower-Z metals, where inclusion of GGA + U had a minimal effect on surface energy ordering . In addition, uranium phases are known to exhibit magnetic moments at their surface, which can affect surface adsorption energies. In order to assess these effects on α-U surface properties and hydrogen adsorption, we have chosen to perform a bounding study using PBE on the faceted (012) and (102) surfaces, which are the two highest energy/most reactive surfaces studied in our work (see Section for further discussion).…”
Section: Resultssupporting
confidence: 71%
“…Shi et al 34 systematically studied the adsorption, dissociation, and diffusion behavior of H on clean and Ti-doped α-U (001) surfaces using density functional theory methods, The study showed that Ti atoms contribute to the bond breaking of H 2 molecules, hydrogen atoms may gather in the region near Ti atoms, and uranium hydrides may nucleate. Morrison and Ray 35 studied the interaction between the H atom and the γ-U (100) surface and showed that the bridge site is most favorable for adsorption, followed by the center site and then the top site. Huang et al 36 compared the adsorption of the H atom and H 2 molecule on the α-U (001) surface using DFT calculations, and the study showed that the top site and the short-bridge site are the most active sites for H atom adsorption, the long-bridge site is the most active site for the decomposition reaction of the H 2 molecule, and the H atoms preferred the triangular central site as the final location.…”
Section: Introductionmentioning
confidence: 99%